From past to future: bibliometric perspective of international research activity on lateral epicondylitis - Boshen Shu; Shufeng Zhang; Jian Gao; Lin Wang; Xiaohui Wang (Frontiers in Surgery)
IntroductionLateral epicondylitis, also termed as “tennis elbow”, is the most common reason for elbow pain and dysfunction. This study aimed to assess the research activity on lateral epicondylitis worldwide.MethodsPublications on lateral epicondylitis from Web of Science database were recorded and analyzed in June 2024. For each article, citations, authors, title, organization, country, journal, year, keywords, topic, and H-index were extracted. VOSviewer and Excel 2020 were used to operate the bibliometric and visualized study.ResultsA total of 913 publications between 1950 and 2023 were included. The total number of citations was 27,866 with the average citation per publication of 31 times. “Orthopedics” became the dominant topic (n = 365, 40.0%). The United States contributed the most publications (n = 201, 22.0%). The latest keywords “platelet rich plasma”, “autologous conditioned plasma”, and “extracorporeal shockwave therapy” mainly appeared since 2018.ConclusionThis bibliometric study indicates that there is a growing trend in the number of publications on lateral epicondylitis. The United States dominated studies of lateral epicondylitis and the Journal of Shoulder and Elbow Surgery was the most productive journal. “Platelet rich plasma”, “autologous conditioned plasma”, and “extracorporeal shockwave therapy” may become new interests in lateral epicondylitis research.